Philippine experimental film practice influences and directions through the films of Roxlee - de Guzman, Anne Marie G. (2004)
In Philippine experimental film practice, the role played by Roxlee is as singular as his name. Ironically, his singularity as a filmmaker rests on a multiplicity of artistic strategies that he utilizes with the ease of a master juggler: animation, dark humor, political commentary, unmitigated nihilism, among others. This paper attempts to tease out the sources of the multiple strands in Roxlee's versatility by locating them in the American avant-garde - not to make the claim that Roxlee actually derived his influences from the US, but rather to see, firstly, where these tendencies come from and lead to; and secondly, how this same set of tendencies may further be elaborated and enriched in local film practice.
Includes bibliographical references (page 64).
Keywords: de Guzman, Anne Marie G